Philosophical content oratory skills biys (Journal of Philosophy Culture and Political Science, 2018)
The article deals with the philosophical facets of oratory of the Kazakh biys. The Kazakh people have always appreciated the content and power of the word. The ability and ability of Kazakhs not only to hear, but also to listen to the word comes from understanding the meaning, content, hidden, hidden meaning and social significance of the word. That is why the Kazakhs say the parent word – the blessed word, the wisdom of ancestors. The art of speech in the traditional worldview was developed not only at the level of elementary speaking, interpersonal communication or mentality, but also at the level of understanding and understanding of the country’s problems, political and legal problems of the nation, and most importantly, had an educational, propaganda and propaganda orientation. The General public is well aware that a comprehensive, holistic study of the spiritual history of the Kazakh people, scientific analysis, rise to a new level, is impossible without the study of the biys. Although Kazakh biys and akyns-songwriters (akyns-Zhyrau) did not create an independent philosophical system, the spiritual world of the Kazakh people developed within the framework of lasting unity and integrity. The purposeof this small study –within the complex of a single public consciousness to highlight and consider thework of biys, their decisions, conclusions, orders, verbal samples, which are the philosophical basis oftheir work, through the study of cognitive teachings to consider and systematize the world of biys from aphilosophical point of view. In General, philosophy is an indicator of a person’s knowledge of the world,freedom of thought and inner freedom. Philosophy is the cornerstone of human thought and wisdom. Italways directs people to ideas, ideals, thoughts that lead to an understanding of the meaning of life. Ifwe consider in this aspect, the Kazakh philosophy, including the worldview of the biys are the basis ofworldview, worldview, evaluation features of the Kazakhs. That is, it is a spiritual space that covers theentire Kazakh national culture.Key words: spiritual revival, biys worldview, oratory, wisdom.